2019
DOI: 10.1021/acs.jmedchem.9b00628
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation, Structure–Activity Relationship, and Mechanism of Action Studies of Quinoline–Metronidazole Derivatives Against Experimental Visceral Leishmaniasis

Abstract: In our efforts to identify novel chemical scaffolds for the development of antileishmanial agents, a series of quinoline–metronidazole hybrid compounds was synthesized and tested against the murine model of visceral leishmaniasis. Among all synthesized derivatives, 15b and 15i showed significant antileishmanial efficacy against both extracellular promastigote (IC50 9.54 and 5.42 μM, respectively) and intracellular amastigote (IC50 9.81 and 3.75 μM, respectively) forms of Leishmania donovani with negligible cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 67 publications
0
30
0
Order By: Relevance
“…Compounds 4-methyl-2-(3-(2-(2-methyl-5-nitro-1H-imidazol-1-yl)ethoxy)phenyl)quinolone (1) and 4methyl-2-(4-(2-(2-methyl-5-nitro-1H-imidazol-1-yl)ethoxy)phenyl)quinolone (2) ( Figure 4) were found to be the most active as determined by a luciferase and 3-(4,5dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, while 2 most effectively inhibited parasites in the liver and spleen of infected mice [49]. To examine NO release in relation to leishmanicidal action, the DAF-2DA dye assay was utilized, which implies local NO formation in living cells at the intracellular level, and revealed 2 leads to oxidative stress through the enhancement of both ROS and NO generation [49]. While these compounds do not contain traditional NO donor groups, these results further show nitrogen oxide species release from 5-nitroimidazoles similar to metronidazole.…”
Section: Metronidazole-no Donor Hybridsmentioning
confidence: 99%
See 3 more Smart Citations
“…Compounds 4-methyl-2-(3-(2-(2-methyl-5-nitro-1H-imidazol-1-yl)ethoxy)phenyl)quinolone (1) and 4methyl-2-(4-(2-(2-methyl-5-nitro-1H-imidazol-1-yl)ethoxy)phenyl)quinolone (2) ( Figure 4) were found to be the most active as determined by a luciferase and 3-(4,5dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, while 2 most effectively inhibited parasites in the liver and spleen of infected mice [49]. To examine NO release in relation to leishmanicidal action, the DAF-2DA dye assay was utilized, which implies local NO formation in living cells at the intracellular level, and revealed 2 leads to oxidative stress through the enhancement of both ROS and NO generation [49]. While these compounds do not contain traditional NO donor groups, these results further show nitrogen oxide species release from 5-nitroimidazoles similar to metronidazole.…”
Section: Metronidazole-no Donor Hybridsmentioning
confidence: 99%
“…Similarly, the mechanism of action of quinoline-metronidazole hybrids was recently investigated against visceral leishmaniasis (VL) [49]. The rationale for merging the two compounds stems from the use of metronidazole to combat experimental VL, especially in combination with other drugs [50][51][52][53], along with the activity of quinolines and their derivatives against in vitro and in vivo forms of experimental and cutaneous VL [54,55].…”
Section: Metronidazole-no Donor Hybridsmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly quinoline-containing pharmaceutical drugs have rendered the strongest biological properties such as antibacterial activity, [30,31] antifungal activity, [32,33] antimalarial activity, [34][35][36] and anti-leishmanial activity. [37][38][39] Alongside this, some review studies reported quinoline scaffolds as remarkable anticancer agents. [40,41] Various action mechanisms have been postulated for the anticancer agents.…”
Section: Introductionmentioning
confidence: 99%